2017
DOI: 10.13005/ojc/330210
|View full text |Cite
|
Sign up to set email alerts
|

Composite Film of Chitosan Loaded Norfloxacin With Improved Flexibility and Antibacterial Activity for Wound Dressing Application

Abstract: This research develops chitosan film incorporated norfloxacin (CH-NOR) designed to combat the infection of bacteria around the wound area. Inclusion of norfloxacin increased the strain-atbreak or flexibility of the film. Swelling behavior and water vapor transmission rates (WVTRs) values are improved and optimum for CH-NOR1.0 film at 524 ± 65 % and 1916 ± 78 g m -2 d -1 , respectively. In-vitro cell studies show that the present of norfloxacin in CH film gradually decreased the number of human dermal fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The slightly lower values with extracts from IBU-loaded membranes were unexpected, as several reports have shown no cytoxicity of IBU for higher concentrations. 57,58 Overall, this assay demonstrated that the scaffolds were compatible with biomedical applications and no acute toxicity was observed.…”
Section: Resultsmentioning
confidence: 68%
“…The slightly lower values with extracts from IBU-loaded membranes were unexpected, as several reports have shown no cytoxicity of IBU for higher concentrations. 57,58 Overall, this assay demonstrated that the scaffolds were compatible with biomedical applications and no acute toxicity was observed.…”
Section: Resultsmentioning
confidence: 68%
“…Previous study has also reported the decreased in swelling behaviour after addition of drugs in film due to the higher compactness in film (increased crosslinking by drug) and hindering the water absorption [18]. Nevertheless, all samples could possibly be used as a wound dressing matrix as the film has a high swelling percentage which is more than 900% [19]. Water Vapour Transmission Rate (WVTR).…”
Section: Resultsmentioning
confidence: 99%
“…The swelling test, and the swelling response (%) was evaluated using a gravimetric method 39 . Each film sample (2 × 2 cm 2 ) was weighed before and after immersion in 20 ml of phosphate buffer (pH 7).…”
Section: Methodsmentioning
confidence: 99%